Non-aqueous electrolyte and secondary battery
By adding the compound shown in Structural Formula 2 to the nonaqueous electrolyte, the lithium salt decomposition product is inhibited and the organic peroxide is stabilized, and the problem of the electrolyte being not resistant to storage is solved, and the long-term storage performance of the nonaqueous electrolyte is improved.
Patent Information
- Application Number
- CN202510106553.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing electrolyte containing organic peroxide is not resistant to storage, resulting in a significant decrease in effective content and cannot meet the needs of long-term storage and commercial applications.
The compound shown in Structural Formula 2 is added to the nonaqueous electrolyte to inhibit the decomposition of lithium salt to produce HF and PF5, thereby stabilizing the organic peroxide shown in Structural Formula 1 and improving its long-term storage performance.
By introducing the compounds shown in Structural Formula 2, the long-term storage performance of organic peroxides is significantly improved, ensuring the consistency of properties of the nonaqueous electrolyte after long-term storage, and avoiding the problem of quality deterioration.
Smart Images

Figure CN119560636A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage electronic components, and in particular relates to a non-aqueous electrolyte and a secondary battery. Background Art
[0002] In recent years, as the application technology of secondary batteries has gradually matured, the market demand for electric vehicles and large-scale energy storage has exploded. In the cutting-edge research of battery technology, high energy density and long cycle life have always been the common goals pursued by the industry. From the technical principle, the core of the long cycle technology of lithium-ion batteries lies in adjusting and optimizing the electrochemical stability of the solid electrolyte interface film (SEI) through electrolyte design. Among them, in the prior art, different film-forming additives are usually added to the electrolyte to change the properties of SEI in the hope of obtaining a more stable SEI component. Effective electrolyte additives will play a key role in the formation of SEI. However, the SEI formed by existing conventional additives has defects, and it is constantly dissolved and reorganized during the charge and discharge process, which not only makes the interface film thicker and increases the impedance, but also consumes active substances and causes capacity decay.
[0003] Organic peroxide is an unstable compound. The -OO- group in its molecular structure is highly chemically active and heat-sensitive. It can undergo self-accelerating decomposition at a specific temperature. It is easily decomposed by heat to produce primary oxygen free radicals. Therefore, it is generally used as an initiator for gel electrolytes in secondary batteries and is consumed before the first charge and discharge formation of the battery. However, there are also reports on the use of organic peroxides as additives for liquid electrolytes. However, due to the insufficient stability of organic peroxides, they need to be used for battery filling and charge and discharge formation in a short time after preparation. During long-term storage, they will decompose and cause a significant decrease in effective content. Therefore, this type of electrolyte is usually not resistant to storage and has no commercial application value. Summary of the invention
[0004] In view of the problem that the existing electrolyte containing organic peroxides is not storable, the present invention provides a non-aqueous electrolyte and a secondary battery.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: The present invention provides a non-aqueous electrolyte, comprising a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive comprises a compound represented by structural formula 1 and a compound represented by structural formula 2: ; wherein n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1, R 2 are not hydrogen at the same time, R1 and R2 are connected to each other to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-12 alkenylene, substituted or unsubstituted C2-12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; ; Wherein, R4, R5, and R6 are each independently selected from a C1-C6 hydrocarbon group, a C6-C20 aryl group, a C3-C6 silicon-containing group, or a C1-C6 fluorinated hydrocarbon group.
[0006] Optionally, in the compound represented by the structural formula 1, R1 is selected from hydrogen, and R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.
[0007] Optionally, in the compound shown in structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl, a substituted or unsubstituted C2-C12 alkenyl, a substituted or unsubstituted C2-C12 alkynyl, or a substituted or unsubstituted C6-C20 aryl.
[0008] Optionally, in the compound represented by structural formula 1, R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0009] Optionally, in the compound represented by structural formula 1, R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.
[0010] Optionally, the compound represented by structural formula 1 includes one or more of the following compounds: .
[0011] Optionally, the compound represented by structural formula 2 includes one or more of the following compounds: .
[0012] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by the structural formula 1 is 0.01% to 1%; and / or Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by structural formula 2 is 0.005% to 0.1%; and / or The mass ratio of the compound represented by the structural formula 1 to the compound represented by the structural formula 2 is 0.2-40.
[0013] Optionally, the non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.
[0014] In another aspect, the present invention provides a secondary battery comprising a positive electrode, a negative electrode and the non-aqueous electrolyte as described above.
[0015] According to the non-aqueous electrolyte provided by the present invention, the compound shown in structural formula 1 and the compound shown in structural formula 2 are added to the non-aqueous electrolyte as additives, wherein the compound shown in structural formula 1 is an organic peroxide, which can participate in the formation of the solid electrolyte interface film (SEI) on the surface of the negative electrode during the first charge and discharge formation of the battery, thereby reducing the irreversible capacity loss of the negative electrode during the battery cycle. However, the inventors have found in practice that although the compound shown in structural formula 1 can be used as a film-forming additive, the non-aqueous electrolyte containing the compound shown in structural formula 1 needs to complete the filling and formation of the battery in a relatively short period of time. During the conventional storage or transportation process, the hydrolysis of the lithium salt (such as LiPF6) in the electrolyte will inevitably produce HF, PF5 and other components. , these components will accelerate the decomposition of the -OO- group in the compound shown in Structural Formula 1, therefore, the non-aqueous electrolyte containing the compound shown in Structural Formula 1 is not storable; to solve this problem, the inventors added the compound shown in Structural Formula 2 to the non-aqueous electrolyte, and unexpectedly found that after the introduction of the compound shown in Structural Formula 2, the long-term storage performance of the compound shown in Structural Formula 1 was improved, indicating that the compound shown in Structural Formula 2 plays a role in stabilizing the compound shown in Structural Formula 1, and its mechanism is: the compound shown in Structural Formula 2 can inhibit the decomposition of lithium salts to produce HF and PF5, and then inhibit the continuous decomposition of the compound shown in Structural Formula 1, thereby ensuring the consistency of the properties of the non-aqueous electrolyte after long-term storage and avoiding the quality degradation problem after long-term storage. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] An embodiment of the present invention provides a non-aqueous electrolyte, including a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive includes a compound shown in Structural Formula 1 and a compound shown in Structural Formula 2: ; wherein n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1, R 2 are not hydrogen at the same time, R1 and R2 are connected to each other to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-12 alkenylene, substituted or unsubstituted C2-12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; ; Wherein, R4, R5, and R6 are each independently selected from a C1-C6 hydrocarbon group, a C6-C20 aryl group, a C3-C6 silicon-containing group, or a C1-C6 fluorinated hydrocarbon group.
[0018] The compound shown in Structural Formula 1 and the compound shown in Structural Formula 2 are added as additives to the non-aqueous electrolyte, wherein the compound shown in Structural Formula 1 is an organic peroxide, which can participate in the formation of the solid electrolyte interface film (SEI) on the surface of the negative electrode during the first charge and discharge formation of the battery, thereby reducing the irreversible capacity loss of the negative electrode during the battery cycle. However, the inventors have found in practice that although the compound shown in Structural Formula 1 can be used as a film-forming additive, the non-aqueous electrolyte containing the compound shown in Structural Formula 1 needs to complete the filling and formation of the battery in a relatively short period of time. During the normal storage or transportation process, the hydrolysis of the lithium salt (such as LiPF6) in the electrolyte will inevitably produce HF, PF5 and other components, which will increase The -OO- group in the compound shown in Structural Formula 1 decomposes rapidly, and therefore, the non-aqueous electrolyte containing the compound shown in Structural Formula 1 is not storable. To solve this problem, the inventors added the compound shown in Structural Formula 2 to the non-aqueous electrolyte, and unexpectedly found that after the introduction of the compound shown in Structural Formula 2, the long-term storage performance of the compound shown in Structural Formula 1 was improved, indicating that the compound shown in Structural Formula 2 played a role in stabilizing the compound shown in Structural Formula 1, and its mechanism is: the compound shown in Structural Formula 2 can inhibit the decomposition of lithium salts to produce HF and PF5, and then inhibit the continuous decomposition of the compound shown in Structural Formula 1, thereby ensuring the consistency of the properties of the non-aqueous electrolyte after long-term storage and avoiding the quality degradation problem after long-term storage.
[0019] In the description of the present invention, the term "C3-C6 silicon-containing group" includes C3-C6 silane groups and fluorinated C3-C6 silane groups.
[0020] In the description of the present invention, the term "C1-C12 alkyl" includes straight-chain alkyl, branched-chain alkyl and cycloalkyl. Similarly, the term "C2-C12 alkenyl" includes straight-chain alkenyl, branched-chain alkenyl and cycloalkenyl. The term "C2-C12 alkynyl" includes straight-chain alkynyl, branched-chain alkynyl and cycloalkynyl. The term "C1-C12 alkylene" includes straight-chain alkylene, branched-chain alkylene and cycloalkylene. The term "C2-C12 alkenylene" includes straight-chain alkenylene, branched-chain alkenylene and cycloalkenylene. The term "C2-C12 alkynylene" includes straight-chain alkynylene, branched-chain alkynylene and cycloalkynylene.
[0021] In the description of the present invention, the term "C1-C12 acyl group" should be understood in a broad sense. Specifically, it can be understood that a single or multiple carbon atoms in a C1-C12 alkyl group are replaced by a carbonyl group. The position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the C1-C12 acyl group is selected from , where R 14 is selected from a single bond or a C1-C11 alkyl group, R 15 An alkyl group selected from C1-C11.
[0022] In the description of the present invention, the term "C2-C12 alkoxy acyl" should be understood in a broad sense. Specifically, it can be understood that a single or multiple carbon atoms in the C2-C12 alkyl group are replaced by The position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the C2-C12 alkoxyacyl group is selected from , where R 16 is selected from a single bond or a C1-C11 alkyl group, R 17 An alkyl group selected from C1-C11.
[0023] In the description of the present invention, the term "C2-C12 ether group" should be understood in a broad sense. Specifically, it can be understood as a C2-C12 alkyl group connecting two adjacent carbon atoms. The number of oxygen atoms in the obtained group may be single or multiple.
[0024] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from hydrogen, R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.
[0025] At this time, the compound shown in the structural formula 1 is a hydroperoxide or an organic peracid. When the compound shown in the structural formula 1 is a hydroperoxide or an organic peracid, it has a higher oxygen content, which can remove reducing impurities in the electrolyte in advance, reduce the amount of gas produced during formation, improve the first coulomb efficiency, and increase the initial discharge capacity of the secondary battery.
[0026] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0027] In some embodiments, in the compound represented by structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl, a substituted or unsubstituted C2-C12 alkenyl, a substituted or unsubstituted C2-C12 alkynyl, or a substituted or unsubstituted C6-C20 aryl.
[0028] At this time, the compound shown in the structural formula 1 is a dialkyl peroxide. When the compound shown in the structural formula 1 is a dialkyl peroxide, it is beneficial to inhibit the co-embedding of solvent molecules and improve the interface compatibility between the electrolyte and the negative electrode.
[0029] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0030] In some embodiments, in the compound represented by structural formula 1, R1 is selected from R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0031] In some embodiments, in the compound represented by structural formula 1, R1 is selected from ; R2 is selected from , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0032] At this time, the compound shown in the structural formula 1 is a diacyl peroxide. When the compound shown in the structural formula 1 is a diacyl peroxide, in addition to having the characteristics of improving the battery cycle life, it can also decompose to form inert carbon dioxide to dilute the explosion limit of the combustible gas when the battery is thermally runaway, which is beneficial to improving the battery safety performance.
[0033] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0034] In some embodiments, in the compound represented by structural formula 1, R1 is selected from R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0035] At this time, the compound shown in the structural formula 1 is a peroxy acid ester. When the compound shown in the structural formula 1 is a peroxy acid ester, the wettability of the electrolyte to the electrode can be improved, the ohmic internal resistance of the battery can be reduced, and the discharge performance of the battery can be improved.
[0036] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0037] In some embodiments, in the compound represented by structural formula 1, R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.
[0038] At this time, the compound shown in the structural formula 1 is a peroxycarbonate or a peroxydicarbonate. When the compound shown in the structural formula 1 is a peroxycarbonate or a peroxydicarbonate, it has the effect of promoting the solvation of lithium ions and improving the lithium diffusion performance inside the battery.
[0039] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0040] In some embodiments, the compound represented by structural formula 1 includes one or more of the following compounds: .
[0041] In some embodiments, the compound represented by structural formula 2 includes one or more of the following compounds: .
[0042] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by Structural Formula 1 is 0.01% to 1%.
[0043] In a specific embodiment, based on the total mass of the non-aqueous electrolyte as 100%, the mass percentage of the compound represented by Structural Formula 1 can be 0.001%, 0.002%, 0.005%, 0.008%, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.28%, 0.3%, 0.32%, 0.34%, 0.35%, 0.38%, 0.4%, 0.42%, 0.44%, 0.45%, 0.48%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two of these values.
[0044] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by Structural Formula 1 is 0.02% to 0.5%.
[0045] The compound shown in Structural Formula 1 participates in the formation of the solid electrolyte interface film (SEI) on the surface of the negative electrode. The solid electrolyte interface film (SEI) formed by the compound shown in Structural Formula 1 can block the direct contact between the non-aqueous electrolyte and the negative electrode, thereby reducing the decomposition and gas generation of the non-aqueous electrolyte on the surface of the negative electrode, and is used to improve the cycle capacity retention rate and high-temperature storage performance of the secondary battery. If the content of the compound shown in Structural Formula 1 is too low, the effect on improving the performance of the secondary battery is limited; if the content of the compound shown in Structural Formula 1 is too high, the probability of side reactions in the electrolyte is increased, and the storage performance of the non-aqueous electrolyte is also deteriorated.
[0046] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by Structural Formula 2 is 0.005% to 0.1%.
[0047] In a specific embodiment, based on the total mass of the non-aqueous electrolyte as 100%, the mass percentage of the compound represented by Structural Formula 2 can be 0.005%, 0.008%, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1% or a range consisting of any two of these values.
[0048] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by Structural Formula 2 is 0.005% to 0.05%.
[0049] The compound shown in Structural Formula 2 and the compound shown in Structural Formula 1 jointly participate in the formation of the solid electrolyte interface film (SEI) on the surface of the negative electrode. More importantly, the compound shown in Structural Formula 2 plays a role in inhibiting the decomposition of the compound shown in Structural Formula 1 in the non-aqueous electrolyte, so as to extend the storage life of the non-aqueous electrolyte. If the content of the compound shown in Structural Formula 2 is too low, the storage performance of the non-aqueous electrolyte will not be significantly improved; if the content of the compound shown in Structural Formula 2 is too high, the film thickness of the solid electrolyte interface film (SEI) on the surface of the negative electrode will be too large, thereby increasing the impedance of the secondary battery.
[0050] In some embodiments, the mass ratio of the compound represented by Structural Formula 1 to the compound represented by Structural Formula 2 is 0.2-40.
[0051] In a specific embodiment, the mass ratio of the compound represented by Structural Formula 1 to the compound represented by Structural Formula 2 can be 0.2, 2.8, 5.4, 8.0, 10.6, 13.2, 15.8, 18.4, 21.0, 23.6, 26.2, 28.8, 31.4, 40.0 or a range consisting of any two of these values.
[0052] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass ratio of the compound represented by Structural Formula 1 to the compound represented by Structural Formula 2 is 4-20.
[0053] The compound shown in structural formula 2 is a Lewis base that can neutralize Lewis acids such as HF and PF5 in the electrolyte, avoiding the consumption of the compound shown in structural formula 1 by components such as HF and PF5, but it will also cause the battery's high-temperature storage performance to deteriorate. If the compound shown in structural formula 1 is used in combination with the compound shown in structural formula 2, the compound shown in structural formula 2 can be used to inhibit the decomposition and consumption of peroxides, and the compound shown in structural formula 1 can also be used to improve the storage degradation caused by the compound shown in structural formula 2, taking into account the long-cycle stability and storage capacity release of the battery.
[0054] The inventors have found through extensive research that when the mass ratio of the compound represented by Structural Formula 1 to the compound represented by Structural Formula 2 is in the range of 0.2 to 40, the two have the best cooperation effect, which can significantly extend the room temperature cycle life of the battery, solve the impedance growth of the battery during high temperature storage, and improve the high temperature storage performance of the battery.
[0055] It should be emphasized that the non-aqueous electrolyte provided in the present application is not a precursor of a gel electrolyte or a solid electrolyte, nor is it suitable as a precursor of a gel electrolyte or a solid electrolyte. The reason is that the improvement of the electrochemical performance of the secondary battery in the present application requires the compounds shown in Structural Formula 1 and the compounds shown in Structural Formula 2 to participate in the formation of the solid electrolyte interface film (SEI) on the negative electrode surface during the battery charge and discharge formation stage, and the compounds shown in Structural Formula 1 and the compounds shown in Structural Formula 2 remaining in the electrolyte to continuously repair the damaged solid electrolyte interface film (SEI) during the long-term cycle of the battery. The precursor of the gel electrolyte or solid electrolyte will undergo a polymerization reaction to form a gel electrolyte before the battery charge and discharge formation. In the polymerization reaction, the organic peroxide shown in Structural Formula 1 reacts with the polymerizable monomer as an initiator, resulting in the consumption of the compound shown in Structural Formula 1, and thus cannot play a corresponding role in the charge and discharge formation and the battery charge and discharge cycle process.
[0056] In some embodiments, the non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.
[0057] In some embodiments, the polymerizable monomers include one or more of acrylate monomers (such as methyl acrylate, ethyl acrylate, butyl acrylate), acrylamide monomers (such as acrylamide, N,N'-methylenebisacrylamide), vinyl compound monomers (such as polyvinyl alcohol, vinyl pyrrolidone, vinyl imidazole), epoxy resin monomers (such as bisphenol A epoxy resin), polyethylene oxide monomers, polyacrylonitrile monomers, and siloxane monomers.
[0058] In some embodiments, the non-aqueous electrolyte does not undergo polymerization reaction under light or heating conditions.
[0059] In some embodiments, the non-aqueous electrolyte is in liquid state after formation.
[0060] In some embodiments, the additive further comprises at least one of a sultone compound, a cyclic carbonate compound, a phosphate compound, a nitrile compound, a lithium salt additive or an alkane compound.
[0061] In some embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propene sultone, and methylene disulfonate.
[0062] In some embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate, or a compound shown in Structural Formula 3: ; In some embodiments, in the structural formula 3, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group.
[0063] In some embodiments, the phosphate compound includes a compound shown in structural formula 4: ; In the structural formula 4, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3.
[0064] In a preferred embodiment, the phosphate compound shown in the structural formula 4 can be at least one of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.
[0065] In some embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, and sebacononitrile.
[0066] In some embodiments, the lithium salt additive includes at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylsulfonyl imide, lithium bispentafluoroethylsulfonyl imide, lithium trifluoromethanesulfonate, lithium monofluorosulfonate, lithium trioxalate phosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium dicyanamide, or a lower aliphatic lithium carboxylate having 4 or less carbon atoms.
[0067] In some embodiments, the alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).
[0068] In other embodiments, the additives may also include other additives that can improve battery performance: for example, additives that enhance battery safety performance, such as flame retardant additives such as fluorophosphates and cyclophosphazenes, or overcharge prevention additives such as tert-amylbenzene and tert-butylbenzene.
[0069] It should be noted that, unless otherwise specified, in general, the content of any one of the optional substances in the additives in the non-aqueous electrolyte is less than 10%, preferably, the content is 0.01-5%, and more preferably, the content is 0.1%~2%. Specifically, the content of any one of the optional substances in the additives can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10% or a range consisting of any two of these values.
[0070] In some embodiments, the additive includes fluoroethylene carbonate, and based on the total mass of the non-aqueous electrolyte being 100%, the content of the fluoroethylene carbonate is 0.01% to 30%.
[0071] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the non-aqueous organic solvent is 65% to 90%.
[0072] Specifically, based on the total mass of the non-aqueous electrolyte as 100%, the mass content of the non-aqueous organic solvent can be 65%, 68%, 71%, 74%, 76%, 78%, 79%, 80%, 81.5%, 82%, 84%, 85%, 86%, 87%, 89%, 90% or a range consisting of any two of these values.
[0073] In some embodiments, the non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent, and a sulfone solvent.
[0074] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether with 3 to 10 carbon atoms and a cyclic ether with 3 to 6 carbon atoms. The cyclic ether may be, but is not limited to, at least one of 1,3-dioxolane, 1,4-dioxane, crown ether, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ether may be, but is not limited to, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. Ether compounds can be used alone or in any combination and ratio. The content of the ether compound is not particularly limited and is arbitrary within the range that does not significantly damage the effect of the high-density lithium-ion battery of the present invention. The volume ratio is usually 1% or more, preferably 2% or more, and more preferably 3% or more, based on the volume ratio of the non-aqueous solvent being 100%. In addition, the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less.
[0075] In some embodiments, the nitrile solvent may specifically be but is not limited to at least one of acetonitrile, glutaronitrile, and malononitrile.
[0076] In some embodiments, the carbonate solvent includes a cyclic carbonate or a chain carbonate, and the cyclic carbonate may be specifically but not limited to at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonate may be specifically but not limited to at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate. The content of the cyclic carbonate is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention, but when one is used alone, the lower limit of its content is usually 3% or more by volume, preferably 5% or more by volume, relative to the total amount of solvent in the non-aqueous electrolyte. By setting this range, the conductivity is reduced due to the reduction in the dielectric constant of the non-aqueous electrolyte, and it is easy to make the large current discharge characteristics of the non-aqueous electrolyte battery, the stability relative to the negative electrode, and the cycle characteristics reach a good range. In addition, the upper limit is usually less than 90% by volume, preferably less than 85% by volume, and more preferably less than 80% by volume. By setting this range, the oxidation / reduction resistance of the non-aqueous electrolyte can be improved, thereby helping to improve the stability during high temperature storage. The content of linear carbonate is not particularly limited, and relative to the total amount of solvent of nonaqueous electrolytic solution, is usually more than 15% by volume, preferably more than 20% by volume, more preferably more than 25% by volume. In addition, usually below 90% by volume, preferably below 85% by volume, more preferably below 80% by volume. By making the content of linear carbonate in above-mentioned scope, easily make the viscosity of nonaqueous electrolytic solution reach appropriate range, suppress the reduction of ionic conductivity, and then contribute to make the output characteristics of nonaqueous electrolyte battery reach good scope. When using two or more linear carbonates in combination, make the total amount of linear carbonate satisfy above-mentioned scope.
[0077] In certain embodiments, it is also possible to preferably use chain carbonates with fluorine atoms (hereinafter referred to as "fluorinated chain carbonates"). The number of fluorine atoms possessed by the fluorinated chain carbonate is not particularly limited as long as it is more than 1, but is generally less than 6, preferably less than 4. When the fluorinated chain carbonate has a plurality of fluorine atoms, these fluorine atoms can be bonded to the same carbon or to different carbons. As the fluorinated chain carbonate, fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, fluorinated diethyl carbonate derivatives, etc. can be listed.
[0078] Carboxylate solvents include cyclic carboxylate and / or chain carbonate. Examples of cyclic carboxylate include at least one of γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Examples of chain carbonate include at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, and butyl propionate.
[0079] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. The content of the sulfone solvent is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. Relative to the total amount of solvent of the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of the sulfone solvent is sufficient to meet the above range. When the content of the sulfone solvent is within the above range, a non-aqueous electrolyte with excellent high temperature storage stability tends to be obtained.
[0080] In a preferred embodiment, the non-aqueous organic solvent comprises a mixture of cyclic carbonate and linear carbonate.
[0081] In some embodiments, the electrolyte salt is selected from lithium salts, including LiPF6, LiODFP, LiODFB, LiBOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, Li2B 10 Cl 10 , lithium chloroborane, lithium trioxalophosphate, a lithium lower aliphatic carboxylate having 4 or less carbon atoms, or at least one of lithium tetraphenylborate.
[0082] In some embodiments, the concentration of the lithium salt in the non-aqueous electrolyte is 0.1 mol / L to 4 mol / L. In a preferred embodiment, the concentration of the lithium salt in the non-aqueous electrolyte is 0.5 mol / L to 2.5 mol / L. Specifically, in the non-aqueous electrolyte, the concentration of the lithium salt can be 0.5mol / L, 0.55mol / L, 0.6mol / L, 0.65mol / L, 0.7mol / L, 0.8mol / L, 0.85mol / L, 0.9mol / L, 0.95mol / L, 1.0mol / L, 1.1mol / L, 1.15mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.45mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2.0mol / L, 2.1mol / L, 2.2mol / L, 2.3mol / L, 2.4mol / L, 2.5mol / L or a range consisting of any two of these values.
[0083] Another embodiment of the present invention provides a secondary battery including a positive electrode, a negative electrode, and the non-aqueous electrolyte as described above.
[0084] In some embodiments, the secondary battery is a lithium-ion battery.
[0085] In some embodiments, the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel oxide (such as lithium nickel oxide), lithium manganese oxide (such as spinel lithium manganese oxide, layered structure lithium manganese oxide, etc.), lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, and one or more of their doping / coating modified compounds. Preferably, the positive electrode active material includes LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z At least one of O2, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.
[0086] In a preferred embodiment, the positive electrode active material is selected from LiFe 1-x’ M' x’ PO4, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1. The lithium-ion battery has a high gram capacity, which can effectively improve the energy density of the battery, and the battery has a charge cut-off voltage of up to 3.8V, a high discharge platform, and shows good cycle stability under the conventional voltage window; and because the iron element is relatively abundant and low in price worldwide, compared with rare and high-priced metals such as cobalt, nickel, and manganese, the use of the above-mentioned positive electrode active material helps to reduce costs and reduce dependence on limited resources.
[0087] In a more preferred embodiment, the positive electrode active material is selected from LiFe 1-x’ Mn x’ PO4, where 0≤x'≤0.5.
[0088] In some specific embodiments, the positive electrode active material may include LiCoO2, LiFePO4, LiFe 0.4 Mn 0.6 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2、LiNi 0.5 Co 0.2 Al 0.3 One or more of O2.
[0089] In some embodiments, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer.
[0090] The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0091] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0092] In some embodiments, the positive electrode current collector includes a metal material that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0093] In some embodiments, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy.
[0094] In a more preferred embodiment, the negative electrode active material includes at least one of graphite, hard carbon, soft carbon, graphene, and silicon-carbon composite materials.
[0095] In some embodiments, the silicon material is one or more of silicon nanoparticles, silicon nanowires, silicon nanotubes, silicon thin films, 3D porous silicon, and hollow porous silicon.
[0096] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer covers the surface of the negative electrode current collector. The negative electrode current collector comprises a metal material that can conduct electrons, preferably, the negative electrode current collector comprises at least one of Al, Ni, tin, copper, and stainless steel, and in a more preferred embodiment, the negative electrode current collector is selected from copper foil.
[0097] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode material layer.
[0098] The negative electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0099] The negative electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0100] In some embodiments, the secondary battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.
[0101] The diaphragm may be an existing conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0102] The present invention is further described below by way of examples.
[0103] Table 1
[0104] Example 1 This example is used to illustrate the preparation method of the non-aqueous electrolyte disclosed in the present invention, which includes the following steps: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC=3:7, and then 1M lithium hexafluorophosphate was added. Based on the total weight of the non-aqueous electrolyte being 100%, components in the mass contents shown in Table 1 were added to obtain a non-aqueous electrolyte.
[0105] Embodiments 2 to 19 Examples 2 to 19 are used to illustrate the non-aqueous electrolyte for lithium ion batteries and the preparation method thereof disclosed in the present invention, and include most of the operating steps in Example 1, except that: In the preparation steps of the non-aqueous electrolyte: Taking the total mass of the non-aqueous electrolyte as 100%, the non-aqueous electrolyte is added with components in the mass percentages shown in Examples 2 to 19 in Table 1.
[0106] Comparative Examples 1 to 11 Comparative Examples 1 to 11 are used to illustrate the non-aqueous electrolyte for lithium ion batteries and the preparation method thereof disclosed in the present invention, and include most of the operating steps in Example 1, except that: In the preparation steps of the non-aqueous electrolyte: Taking the total mass of the non-aqueous electrolyte as 100%, the non-aqueous electrolyte is added with components in the mass percentages shown in Comparative Examples 1 to 11 in Table 1.
[0107] Performance Testing The non-aqueous electrolytes prepared in the above Examples 1 to 19 and Comparative Examples 1 to 11 were stored at 25° C. for 30 days, and the content of the compound represented by Structural Formula 1 after storage was detected to calculate the remaining percentage of the compound represented by Structural Formula 1, which was recorded in Table 2; the acidity of the non-aqueous electrolyte before and after storage was detected, and the acidity growth rate was calculated based on the acidity of the non-aqueous electrolyte before and after storage and recorded in Table 2.
[0108] Table 2
[0109] It can be seen from the test results of Examples 1 to 10 and Comparative Examples 1 to 8 that by introducing the compound of Structural Formula 2 into the non-aqueous electrolyte containing the compound of Structural Formula 1, the long-term storage performance of the non-aqueous electrolyte is significantly improved, while in the non-aqueous electrolyte not containing the compound of Structural Formula 2, the compound of Structural Formula 1 shows a significant decrease after 30 days of storage, indicating that the compound of Structural Formula 2 can effectively stabilize the compound of Structural Formula 1, and the compound of Structural Formula 2 can inhibit HF and PF5 produced by the decomposition of lithium salts, thereby preventing the compound of Structural Formula 1 from continuously decomposing. This mechanism ensures that the non-aqueous electrolyte can maintain the consistency of properties after long-term storage, avoiding the problem of quality degradation caused by long-term storage.
[0110] It can be seen from the test results of Examples 1 to 6 that as the content of the compound represented by Structural Formula 2 gradually increases, its decomposition inhibition effect on the compound represented by Structural Formula 1 shows a trend of first increasing and then decreasing, indicating that an appropriate amount of the compound represented by Structural Formula 2 can inhibit the decomposition of the compound represented by Structural Formula 1, but an excessive amount of the compound represented by Structural Formula 2 will affect its inhibitory effect, presumably because an excessive amount of Structural Formula 2 itself will cause a reaction with the compound represented by Structural Formula 1.
[0111] It can be seen from the test results of Examples 4, 8 to 15 and Comparative Examples 1 to 7 that when the content of the compound represented by Structural Formula 2 is constant, as the content of the compound represented by Structural Formula 1 gradually increases, the storage decomposition inhibition effect on the compound represented by Structural Formula 1 also shows a trend of first increasing and then decreasing, indicating that the compound represented by Structural Formula 2 has a relatively poor decomposition inhibition effect on an excess or trace amount of the compound represented by Structural Formula 1.
[0112] It can be seen from the test results of Examples 16 to 19 and Comparative Examples 8 to 11 that when different types of compounds represented by Structural Formula 1 and different types of compounds represented by Structural Formula 2 are combined, they can all inhibit the decomposition of the compound represented by Structural Formula 1 to varying degrees.
[0113] Embodiments 20 to 38 Examples 20 to 38 are used to illustrate the preparation method of the lithium ion battery disclosed in the present invention, which includes the following steps: 1) Electrolyte Examples 20 to 38 respectively use the non-aqueous electrolytes of Examples 1 to 19 after being stored at 25° C. for 30 days.
[0114] 2) Preparation of positive electrode The positive electrode active material lithium iron phosphate, conductive carbon black (Super-P) and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 93:4:3, and then dispersed in N-methylpyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and cut with a mold to obtain a positive electrode plate with a thickness of 120-150μm.
[0115] 3) Preparation of negative electrode The negative electrode active material artificial graphite, conductive carbon black (Super-P), binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain negative electrode slurry. The slurry is coated on both sides of the copper foil, dried, rolled and vacuum dried, and cut with a mold to obtain the negative electrode plate, the thickness of the plate is 120-150μm.
[0116] 4) Preparation of battery cells A three-layer separator with a thickness of 20 μm is placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator is stacked. An ultrasonic welder is used to weld aluminum lead wires to the positive plate and nickel lead wires to the negative plate. The cells are placed in a shaped aluminum foil packaging bag and sealed on the top and sides. After vacuum baking at 75°C for 48 hours, the cells are completely encapsulated to obtain the battery cells ready for liquid injection.
[0117] 5) Battery filling and formation In a glove box with a dew point controlled below -40°C, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left to stand for 24 hours before the first charge formation was performed.
[0118] Comparative Examples 12~22 Comparative Examples 12 to 22 are used to compare and illustrate the method for preparing a lithium ion battery disclosed in the present invention, and include most of the operating steps in Examples 20 to 38, except that: As shown in Table 3, Comparative Examples 12 to 22 respectively use the non-aqueous electrolytes of Comparative Examples 1 to 11 stored at 25° C. for 30 days.
[0119] Performance Testing The lithium-ion battery prepared above was subjected to the following performance tests: (1) Battery first coulombic efficiency test: During the first charging and formation process of the battery, record the charging capacity. After formation, discharge the battery and record the discharge capacity. Calculate the first coulombic efficiency: first coulombic efficiency (%) = discharge capacity / charge capacity*100%.
[0120] (2) Battery room temperature cycle performance test: The divided batteries were subjected to room temperature cycle test in a constant temperature environment of 25°C with the following steps: 1C constant current and constant voltage charging to 3.65 V, cut-off current 0.05C, and then discharged to 2.5 V at 1.5C constant current after being left alone, and left alone for 5 minutes. This charge and discharge cycle was repeated for 2000 cycles. The discharge capacity of each cycle was recorded, and the cycle capacity retention rate (%) = 2000th cycle discharge capacity / first cycle discharge capacity * 100%, and the average value of the parallel test samples was calculated.
[0121] The test results obtained are entered in Table 3.
[0122] Table 3
[0123] It can be seen from the test results of Examples 20 to 38 and Comparative Examples 12 to 22 that after 30 days of storage, when the non-aqueous electrolyte containing both the compound represented by Structural Formula 1 and the compound represented by Structural Formula 2 is applied to a lithium-ion battery, the initial coulombic efficiency and cycle capacity retention rate of the lithium-ion battery can be effectively improved, while the non-aqueous electrolyte containing only the compound represented by Structural Formula 1 has a significant problem of decreased battery performance. Moreover, combined with the test results of Table 2, it can be seen that the initial coulombic efficiency and cycle capacity retention rate of the lithium-ion battery are related to the content of the compound represented by Structural Formula 1 in the non-aqueous electrolyte, indicating that the compound represented by Structural Formula 2 can inhibit the decomposition of the compound represented by Structural Formula 1 during storage, thereby helping to improve the storage stability of the non-aqueous electrolyte, and ensure that a sufficient amount of the compound represented by Structural Formula 1 remains in the non-aqueous electrolyte after storage for a certain period of time, thereby improving the cycle performance of the lithium-ion battery through the compound represented by Structural Formula 1.
[0124] It can be seen from the test results of Examples 1 to 15 that when the mass ratio of the compound represented by Structural Formula 1 to the compound represented by Structural Formula 2 is 4 to 20, the cycle performance and the first coulombic efficiency of the obtained lithium-ion battery are optimal, indicating that at this ratio, the compound represented by Structural Formula 1 and the compound represented by Structural Formula 2 show a synergistic effect, which can not only utilize the compound represented by Structural Formula 2 to inhibit the decomposition and consumption of peroxide, but also utilize the compound represented by Structural Formula 1 to improve the storage degradation caused by the compound represented by Structural Formula 2, taking into account the long cycle stability and storage capacity release of the battery.
[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A non-aqueous electrolyte, characterized in that: It includes a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive includes a compound shown in Structural Formula 1 and a compound shown in Structural Formula 2: ; wherein n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1, R 2 are not hydrogen at the same time, R1 and R2 are connected to each other to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-12 alkenylene, substituted or unsubstituted C2-12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; ; Wherein, R4, R5, and R6 are each independently selected from a C1~C6 hydrocarbon group, a C6~C20 aryl group, a C3~C6 silicon-containing group or a C1~C6 fluorinated hydrocarbon group.
2. The non-aqueous electrolyte according to claim 1, characterized in that In the compound represented by the structural formula 1, R1 is selected from hydrogen, R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.
3. The non-aqueous electrolyte according to claim 1, characterized in that In the compound represented by structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl group, a substituted or unsubstituted C2-C12 alkenyl group, a substituted or unsubstituted C2-C12 alkynyl group, or a substituted or unsubstituted C6-C20 aryl group.
4. The non-aqueous electrolyte according to claim 1, characterized in that In the compound represented by the structural formula 1, R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
5. The non-aqueous electrolyte according to claim 1, characterized in that In the compound represented by the structural formula 1, R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.
6. The non-aqueous electrolyte according to claim 1, characterized in that The compound represented by the structural formula 1 includes one or more of the following compounds: 。 7. The non-aqueous electrolyte according to claim 1, characterized in that The compound represented by the structural formula 2 includes one or more of the following compounds: 。 8. The non-aqueous electrolyte according to claim 1, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by the structural formula 1 is 0.01% to 1%; and / or Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by structural formula 2 is 0.005% to 0.1%; and / or The mass ratio of the compound represented by the structural formula 1 to the compound represented by the structural formula 2 is 0.2-40.
9. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.
10. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the non-aqueous electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Nonaqueous electrolyte of lithium ion battery and lithium ion battery
CN107666007A
Non-aqueous electrolyte and lithium ion battery
CN116190788A
Electrolyte for lithium cell and lithium cell containing the same
CN1495961A
Lithium secondary battery
CN1930726A
Nonaqueous electrolyte for lithium secondary battery, and lithium secondary battery using the same
JP2006222064A